Rethinking the Islamic Education Curriculum: A Sociological Review - Adyan Dhio Akhdany; Rafli Hidayat; Muhammad Abdullah Darraz (Lembaga Yasin AlSys, 2026)
This study examines the sociological foundations and transformative imperatives of the Islamic Education (Pendidikan Agama Islam/PAI) curriculum in Indonesia. Using a systematic literature review of theoretical and empirical sources, this study explores how sociological principles, including culture, social structure, and community needs, shape curriculum design and implementation amid rapid social, technological, and cultural change. The analysis identifies Industry 4.0, digital disruption, and the persistent dichotomy between religious and secular knowledge as major drivers of curriculum renewal, while national reforms such as the Independent Curriculum (Kurikulum Merdeka) and emerging models such as the Love-Based Curriculum (Kurikulum Berbasis Cinta/KBC) provide strategic opportunities for transformation. The findings indicate that a sociologically informed PAI curriculum can strengthen epistemological integration, wasathiyah moderation, and contextualized character education by connecting religious texts with contemporary social issues, promoting community engagement, and embedding ICT and digital literacy. However, implementation remains constrained by uneven educator digital competence, infrastructure disparities, and limited integration of Islamic values into digital learning content. This study concludes that PAI curriculum transformation should prioritize interdisciplinary thematic instruction, authentic assessment, and partnerships among schools, families, and communities to produce graduates who are ethically grounded, socially responsible, and technologically competent. The study contributes to the discourse on Islamic education reform by proposing a dynamic and integrative PAI curriculum that reconciles tradition and modernity, enhances educational relevance, strengthens social cohesion, and supports the formation of moral and civic-minded citizens capable of addressing twenty-first-century challenges.